NUMERICAL STUDY OF DODECANE’S COMBUSTION IN THE BURNER CHAMBER - Askarova, A. S.; Bolegenova, S. A.; Ryspayeva, M. Zh.; Voloshina, I. E. (Recent Contributions to Physics, 2009)
In this work the distributions of maximum temperature depending of the spray velocity, time distributions of the fuel vapor concentration and temperature in the space of the burner chamber for the effective velocity have been obtained in order to research the dodecane’s combustion process in the chamber.